An Information Quality Framework for Managed Health Care - Crossette-Thambiah G; Berleant D; AbuHalimeh A (Journal of Healthcare Leadership)
Grace Crossette-Thambiah, Daniel Berleant, Ahmed AbuHalimeh Department of Information Science, University of Arkansas at Little Rock, Little Rock, AR, USACorrespondence: Daniel Berleant, Email jdberleant@ualr.eduIntroduction: Data and information quality play a critical role in the managed healthcare sector, where accurate and reliable information is crucial for optimal decision-making, operations, and patient outcomes. However, managed care organizations face significant challenges in ensuring information quality due to the complexity of data sources, regulatory requirements, and the need for effective data management practices. The goal of this article is to develop and justify an information quality framework for managed healthcare, thereby enabling the sector to better meet its unique information quality challenges.Methods: The information quality framework provided here was designed using other information quality frameworks as exemplars, as well as a qualitative survey involving interviews of twenty industry leaders structured around 17 questions. The responses were analyzed and tabulated to obtain insights into the information quality needs of the managed healthcare domain.Results: The novel framework we present herein encompasses strategies for data integration, standardization and validation, and is followed by a justification section that draws upon existing literature and information quality frameworks in addition to the survey of leaders in the industry.Discussion: Emphasizing objectivity, utility, integrity, and standardization as foundational pillars, the proposed framework provides practical guidelines to empower healthcare organizations in effectively managing information quality within the managed care model.Keywords: data quality, information quality, information quality framework, managed healthcare, managed health care, data management, data governance